Reflection of micro-waves from earth’s surface (MAUSAM, 1960)
Interesting examples of coeflicient of reflection from flat ground (aerodrome runway) have been described. These observations also indicate the satisfactory performance of the radar set installed at Dum Dum airport for meteorological purposes.             Different aspects of the occurrence of reflection phenomenon have been discussed. A review of the work done in this respect in other ceuntries has also been made.